Case report: Primary pleural low-grade fibromyxoid sarcoma in a 4-year-old boy with molecular confirmation - He, Xiangni; Jing, Wenyi; He, Xin; Chen, Min; Zhang, Hongying (Frontiers in Oncology, 2023)
Low-grade fibromyxoid sarcoma (LGFMS) is a rare malignant fibroblastic tumor, principally affecting the deep tissues of the proximal trunk and extremities in young adults. However, primary pleural LGFMS is extremely rare, and only three cases have been reported in the previous English literature without genetic confirmation.Furthermore, the historical pleural LGFMS cases were all adults, and the primary pleural LGFMS in children has never been reported to date. Here, we presented a primary pleural LGFMS in a 4-year-old boy with detailed clinical, pathological, and molecular results. Histologically, the current tumor showed typical alternating collagenous and myxoid areas, containing spindled or oval tumor cells arranged in a whorled and short fascicular pattern. In some areas, the tumor cells exhibited moderate atypia and mitotic figures were identified but without the identification of giant collagen rosettes. Immunohistochemically, all the neoplastic cells showed strong and diffuse positivity for MUC4. Genetically, FUS gene rearrangement was revealed by fluorescence in situ hybridization (FISH), and subsequently next-generation sequencing (NGS) and polymerase chain reaction (PCR) further demonstrated the FUS::CREB3L2 fusion transcript. To the best of our knowledge, this is the first case of primary pleuralLGFMS with the identification of FUS gene rearrangement and FUS::CREB3L2 fusion in a 4-year-old child. Our study expands the age range of pleural LGFMS and highlights the combination of morphology, immunohistochemical and molecular analysis in such challenging cases.